SUSTAINABLE BUSINESS COMPETITIVENESS: TRANSLATING CONCEPT INTO PRACTICE - Idqan Fahmi (Jurnal Manajemen & Agribisnis, 2012)
Globalization has proven to spur economic growth for many countries in the world. It has, however, also negative impacts in terms of widening income gap, environmental degradation etc. such that many are worried that the growth will not be sustainable. Triple bottom line was introduced to make the economic growth and company competitiveness more sustainable. Although to define the concept is easy, to make it implemented, especially by developing countries, is another matter. Education and research track by universities is suggested to be one best way to accelerate the implementation of the concept. A case of Graduate Program of Management and Business (MB-IPB) is used to illustrate the attempt.Keywords: Sustainable Business Competitiveness, Triple Bottom Line, MB-IPB, 3PsABSTRAKGlobalisasi telah terbukti memacu pertumbuhan ekonomi pada berbagai belahan dunia, tetapi juga mempunyai banyak dampak negatif yang dirasakan dalam bentuk melebarnya kesenjangan pendapatan, kerusakan lingkungan dll. Akibatnya banyak khawatir bahwa pertumbuhan ekonomi yang terjadi tidak akan berkelanjutan. Konsep Triple Bottom Line diperkenalkan untuk membuat pertumbuhan ekonomi dan dayasaing perusahaan lebih berkelanjutan. Walaupun konsep ini relatif mudah untuk dijelaskan, menerapkannnya ternyata tidak mudah, terutama di negara berkembang. Jalur pendidikan dan penelitian merupakan salah satu cara terbaik yang dapat dilakukan universitas untuk mempercepat penerapan konsep. Kasus Program Pascasarjana Manajemen dan Bisnis (MB-IPB) digunakan untuk mengilustrasikan upaya tersebut.Kata kunci: Dayasaing Bisnis Berkelanjutan, Triple Bottom Line, MB-IPB, 3P